Income Inequality and Export Prices Across Countries - Eckhard Janeba; Lisandra Flach (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper provides first firm-level evidence on the links between income inequality within a country and the patterns of trade and export prices. We identify a theoretical mechanism behind these links, which relates income inequality to product quality and prices using a simple demand composition effect. Theory suggests that a more unequal distribution of income leads to higher average prices, in particular in middle-income countries. The predictions are confirmed using detailed firm and product level data. Controlling for income per capita, prices are systematically higher in more unequal destination countries, with this effect being particularly relevant for middle-income countries. Our results are robust to different measures of income distribution, hold only for differentiated goods and in particular for products with a high degree of vertical differentiation.
Keywords: F12; F14; L11; 330